VGluT1 Deficiency Impairs Visual Attention and Reduces the Dynamic Range of Short-Term Plasticity at Corticothalamic Synapses. (11th November 2019) - Lindström, Sarah H; Sundberg, Sofie C; Larsson, Max; Andersson, Fredrik K; Broman, Jonas; Granseth, Björn
Abstract: The most common excitatory neurotransmitter in the central nervous system, glutamate, is loaded into synaptic vesicles by vesicular glutamate transporters (VGluTs). The primary isoforms, VGluT1 and 2, are expressed in complementary patterns throughout the brain and correlate with short-term synaptic plasticity. VGluT1 deficiency is observed in certain neurological disorders, and hemizygous (VGluT1 +/− ) mice display increased anxiety and depression, altered sensorimotor gating, and impairments in learning and memory. The synaptic mechanisms underlying these behavioral deficits are unknown. Here, we show that VGluT1 +/− mice had decreased visual processing speeds during a sustained visual-spatial attention task. Furthermore, in vitro recordings of corticothalamic (CT) synapses revealed dramatic reductions in short-term facilitation, increased initial release probability, and earlier synaptic depression in VGluT1 +/− mice. Our electron microscopy results show that VGluT1 concentration is reduced at CT synapses of hemizygous mice, but other features (such as vesicle number and active zone size) are unchanged. We conclude that VGluT1-haploinsuficiency decreases the dynamic range of gain modulation provided by CT feedback to the thalamus, and this deficiency contributes to the observed attentional processing deficit. We further hypothesize that VGluT1 concentration regulates release probability by applying a "brake" to an unidentified presynaptic protein that typically acts as a positive regulator of release.